Interventions for the promotion of motor activities in primary school. Assessment of motor performance in relation to perceived self-efficacy and enjoyment - Colella, Dario; Bellantonio, Sergio; D'Arando, Cristina; Monacis, Domenico (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
Overweight and obesity in childhood are factors influencing the motor development of children. This study aims to present the results of a cross-sectional study aimed at assessing and comparing motor performance, perceived self-efficacy and enjoyment in relation to body mass index (BMI) in a sample of primary school children. The surveys were carried out as part of the SBAM regional project, aimed at the third classes of primary schools in Apulia region to promote correct lifestyles. The sample of 1850 pupils (F: 933; M: 917) was divided into groups according to gender differences and BMI (normal weight vs overweight vs obese). Motor performance was assessed with four engine tests (SLJ; 6 MWT; 10x4; MBT); perceived self-efficacy and enjoyment with two self reports: PSP_C and PACES. In addition to the descriptive statistics (M ± SD), the analysis of variance and correlation was performed to highlight the differences between the groups. The data showed a strong relationship between BMI and motor performance, perceived self-efficacy and enjoyment in both sexes. Children with high BMI showed lower motor performance and perceived self-efficacy scores and enjoyment than the normal weight group (p <.05). The results of the present study suggest that higher BMI values not only negatively affect motor performance, and therefore represent an indicator of low motor development, but are also associated with reduced levels of perceived self-efficacy and enjoyment